(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
Baron beach is a specific habitat due its characteristic as a narrow beach with outlet of sub-surface rivers. This research had been done in order to know its microbial characteristic. Research used survey method and bacterial identification was done based on comparative description. The research showed that during high tide of seawater, the total bacterial count was 1.0 to 6.0 x 107 cfu/ml on NA and 2.0 to 7.0 x 107 cfu/ml on NA+0.5% NaCl. Furthermore, during the low tide of sea water, the total bacterial count was 1.4 to 8.8 x 108 cfu/ml on NA, and 3.2 to 9.0 106 cfu/ml on NA+0,5% NaCl. This study found 14 genera of bacteria and dominated by Gram-negative bacteria. The result indicated seawater influenced the number of bacteria present in this environment. Â© 2003 Jurusan Biologi FMIPA UNS Surakarta Key words: bacteria, aerobic-heterotrophic, Baron